The Non-Linear Relationship Between CEO Compensation Incentives And Corporate Tax Avoidance - Chee, Seungmin; Choi, Wooseok; Shin, Jae Eun (Journal of Applied Business Research, 2017)
This study examines the effect of CEO compensation incentives on corporate tax avoidance. Unlike prior literature that assumes a monotonic relation between executive compensation incentives and tax avoidance, we find a non-linear relation between the two. Specifically, we find that CEO compensation incentives exhibit a positive relation with corporate tax avoidance at low levels of compensation incentives, whereas they show a negative relation at high levels of compensation incentives. We further find that the non-linear relationship between CEO compensation incentives and corporate tax avoidance does not exist for the subsample of S&P500 firms. Collectively, we provide evidence of the two counter effective forces, namely, - the incentive alignment effect and the risk-reducing effect, - that help explain the effect of CEO compensation incentives on tax avoidance.
Keywords: Tax Avoidance; CEO Compensation Incentives; Risk-Taking Activities